TREATMENT OF UNCOMPLICATED AND COMPLICATED HYPERTENSIVE CRISIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
A hypertensive crisis is “an acute, pronounced increase in blood pressure, accompanied by clinical symptoms and requiring an immediate, controlled reduction in order to prevent or limit target organ damage” [1]. The key point in this definition is not the level of blood pressure (BP), but the severity of clinical symptoms; this is what is most important for diagnosing the type of hypertensive crisis and choosing further tactics for patient management. However, the accuracy of blood pressure measurements is also important.